A model of lung parenchyma stress relaxation using fractional viscoelasticity. Issue 8 (August 2015) - Dai, Zoujun; Peng, Ying; Mansy, Hansen A.; Sandler, Richard H.; Royston, Thomas J.
Highlights Lung parenchyma viscoelasticity was studied via stress relaxation. Stress relaxation studies were conducted on freshly exercised inflated pig lungs. Fractional order and integer order viscoelastic models were compared. Fractional standard linear solid was the best among four-parameter models.